The Eff ffectt off Septtopllastty on IInfferr iiorr Turrbiinatte Siize - Rasheed, Ahmed Muhei; Homadi, Nibras Jassam; Al-Salami, Azzam M.A. (AL-Kindy College Medical Journal, 2014)
Bac kground:: Septal deviation is one of the commonest anatomical deformities of the nasal skeleton, this deviation is usually accompanied by compensatory hypertrophy of the inferior turbinate on the concave side that will accentuate the severity of nasal obstruction.Objectives: To evaluate the effect of septoplasty on the size of the inferior turbinate in patients with nasal septum deviation.Methods: This is a prospective study of 25 patients attending the otolaryngological department at Al-Jirahat teaching hospital from September 2011 to November 2013, complaining mainly of nasal obstruction. Otolaryngological examination had shown nasal septum deviation. The cross sectional areas of inferior turbinates were measured with computed tomography preoperatively & one year postoperatively. All the patients were treated by septoplasty alone without inferior turbinate surgery. Res ull tts :: The cross-sectional areas of inferior turbinates on the concave side were significantly decreased after 1 year of septoplasty, & significantly increased on the convex side. Conc llus iions :: Septoplasty alone without turbinate surgery in patients with nasal septum deviation & compensatory inferior turbinate hypertrophy may be effective in reversing the size of inferior turbinate.